Pediatric Tui Na for cough in children: A systematic review and meta-analysis of randomized controlled trials - Hui Mao; Yue-hui Wei; Hui-ming Su; Zi-yun Jiang; Xun Li (Elsevier, 2022)
Objectives: To evaluate the effectiveness and safety of pediatric Tui Na for the treatment of cough in children under seven years of age.Design: Systematic review and meta-analysis of randomized controlled trials. Methods: We searched seven major databases and two ongoing trial registers before November 2021 for randomized controlled trials (RCTs) on pediatric Tui Na for cough in children. Main outcome measures were cough related status (such as cough frequency, severity, and duration), use of western medicines, quality of life, medical costs, recurrence rate, adverse events and acceptance. Two reviewers independentlyselected studies and extracted data. Results were presented by RevMan 5.4 as risk ratios (RRs) and mean differences (MDs), both with 95 % confidence intervals (CIs). Risk of bias were assessed using ROB tools and quality of evidence by GRADE. Results: Sixteen RCTs involving 1502 participants were included in this review. Most trials were poor in quality for not reporting allocation concealment, blinding of outcomeassessment or outcome data completeness. The pooled results demonstrated that pediatric Tui Na alone (2 RCTs, 205 participants; MD −2.22, 95 %CI −3.71 to −0.73; P = 0.004; I 2 = 90 %; low certainty) or combined with conventional treatment (7 RCTs, 668 participants; MD −1.66, 95 %CI −2.89 to −0.44; P = 0.008; I 2 = 98 %; low certainty) shortened cough duration. The combined treatment also decreased the recurrence rate of cough (3 RCTs, 135 participants; RR 0.35, 95 %CI 0.21-0.58; P < 0.0001; I 2 = 0 %; moderate certainty). There were insufficient data on adverse events. Conclusions: This review indicates that pediatric Tui Na may shorten the course and decrease the recurrence rate of cough in children, and appears to be relatively safe. However, large-sample, multi-center and high-quality RCTs are warranted to confirm these findings.